Aberrant salience in first‐episode psychosis: Longitudinal stability and treatment‐response. Issue 8 (16th November 2021) - Scazza, Ilaria; Pelizza, Lorenzo; Azzali, Silvia; Garlassi, Sara; Paterlini, Federica; Chiri, Luigi Rocco; Poletti, Michele; Pupo, Simona; Raballo, Andrea
Abstract: Aim: Aberrant salience (AS) is considered a putative predisposing factor for the onset of psychosis. However, despite several studies conducted in the general population, research in early psychosis is still relatively scarce. The main purposes of this study were to investigate any relevant correlation of AS with functioning and psychopathology in young patients with first episode psychosis (FEP), and to analyse the longitudinal stability of AS across a 1 year follow‐up period. Methods: All the participants (139 FEP), aged 13–35 years, completed the Aberrant Salience Inventory (ASI), the Comprehensive Assessment of At‐Risk Mental States (CAARMS), and the Positive And Negative Syndrome Scale (PANSS). Spearman correlation analysis among psychopathological parameters were performed both at baseline and after the 1 year of follow‐up. Results: Across the follow‐up, FEP patients showed a significant decrease in the ASI total score. This reduction was specifically associated with the number of individual cognitive‐behavioural therapy sessions offered to FEP individuals in the same time period (and not with antipsychotic dose at baseline). Conclusions: AS is clinically significant in FEP patients. However, it tends to ameliorate over time together with the delivery of specialized, person‐tailored FEP treatments within a specific "Early Intervention in Psychosis" protocol.